A Single-Phase Consensus-Based Optimization Strategy for Three-Phase Four-Wire Microgrids - Espina-Gonzalez, E; Diaz-Diaz, M; Pizarro-Jimenez, P (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper proposes a new single-phase consensus-based distributed secondary control strategy for frequency control, optimal dispatch (OD) and phase shift regulation in isolated three-phase four-wire microgrids (MGs). Moreover, the proposed scheme maintains all the converter-based generators (CBG) within operation limits. The dispatch of the single-phase CBGs complies with the Karush-Kuhn-Tucker (KKT) conditions of a linear optimal power flow (OPF) formulation. Furthermore, since the power dispatch is considered in single-phase CBGs, the voltage phase difference is not maintained at 120°. Therefore, the proposed algorithm also corrects this condition and restores the voltage phase difference to the balanced condition. Only local measurements and information from the neighbours are needed to achieve the aforementioned characteristics, which allows for considering a distributed architecture. The good performance of the controllers proposed in this article is validated through extensive simulation tests,driving the system to an optimal economic operation. © 2023 IEEE.